The Mechanical Properties of Different alloys in friction stir processing: A Review. (2018) - Chaudhary, Anshul; Kumar Dev, Abhishek; Goel, Anshul; Butola, Ravi; Ranganath, M.S.
Abstract: This review paper deals with the consequences of Friction Stir Processing on different alloys like Mg-4Y-3Nd(WE43), Mg-ZrSiO4 -N2 O3, Al-Si hypoeutectic A356 alloy, 5210 steel (WC-12% CO coated). These effects can be on mechanical properties like strength, hardness, machinability, tensile strength. FSP leads to grain growth and refinement of grains into fine structure. FSP is carried out by FSP tool at different speeds and angles which results in difference of properties in the friction stir processed alloy. FSP can be widely used in metals such as aluminium and magnesium that are lightweight and can be used extensively in various applications; but due to certain lack in strength and hardness they are not used in their original form and require certain processing to obtain desired properties.